AN ATTENUATION-BASED SEDIMENT CLASSIFICATION TECHNIQUE USING CHIRP SUB-BOTTOM PROFILER DATA AND LABORATORY ACOUSTIC ANALYSIS - Stevenson I.R.; McCann C.; Runciman P.B. (My University, 2002)
A remote sediment classification technique based on attenuation measurements from Chirp sub-bottom profiler data is described. This differs from previously published work in that attenuation measurements are obtained for each stratigraphic unit within a complex, thinly interbedded sedimentary sequence. Compressional wave attenuation measurements are obtained for a wide variety of lithologies, including muds, silts, sands, clayey sands, silty clays and gravel lags, with grain sizes ranging from 8 Phi to -4 Phi. In addition, attenuation measurements from sub-bottom profiler data were calibrated against laboratory acoustic measurements of vibracores and seabed samples from corresponding geographic locations, under simulated in-situ conditions using a Pulse Tube method. We adapt an instantaneous frequency matching method using a causal attenuation filter to model the decay of the Chirp transmitted waveform. From this modelling, a relationship between t* (a causal attenuation operator) and change in instantaneous frequency is established. The Hilbert transform is used to extract instantaneous frequency information from Chirp seismic, which is used to derive attenuation information for selected individual stratigraphic layers imaged by the sub-bottom profiler. This paper draws attention to the limitations in comparing attenuation measurements derived from Chirp sub-bottom profiler data against previously published literature on experimental attenuation measurements, which are limited by the wide variance of these data, and the difficulty in finding a meaningful best fit to these data. This demonstrates the importance of calibrating remote sediment classification observations using complimentary acoustic analysis of seabed samples to generate a site-specific geoacoustic database. A positive correlation between laboratory and sub-bottom profiler attenuation measurements was obtained, with a correlation coefficient of 0.885. Poorly sorted gravels with a mixed lithic and biogenic pebble component are characterised by very high attenuation with values of Q from 4 to 19. These sediments are considerably coarser-grained than those typically described in previously published experimental studies.
Keywords: ATTENUATION; CHIRP SUB-BOTTOM PROFILER; SEDIMENT CLASSIFICATION